Village Health Sanitation and Nutrition Committees: reflections on strengthening community health governance at scale in India. (3rd October 2018) - Ved, Rajani; Sheikh, Kabir; George, Asha S; VR, Raman
Abstract : India's National Health Mission constituted Village Health Sanitation and Nutrition Committees (VHSNCs) as a key mechanism for community health governance. Health committees provide citizens with the opportunity to shape health systems and policies. Yet much remains to be learnt on how best to sustain health committees as vehicles for community health governance at scale. This paper reflects on the authors' experiences of introducing revised guidelines and an institutional support package for VHSNCs in two pilot settings in India and outlines lessons we learnt for sustaining community health governance at geographic scale. We describe the importance of ensuring norms for equitable participation, aligning committee rules with existing forms of decentralised government and providing key supports in terms of engaging NGOs as key implementation facilitators. Integration with rigid and unresponsive government administrative structures however remains a persistent challenge for scaling up health committees. With sustained financial support and strategic deployment of key personnel, VHSNCs could pave the way for more equitable and effective community participation in health governance at scale.